Risk identification of Halal products among young Muslim consumers in Malaysia - Azmi, Anis Zafirah; Ahmad Ridzuan, Ahmad Nur Azam; Mohamad Razi, Nor Faezah; Azeman, Siti Nur Aisyah (Universiti Teknologi MARA, Perak, 2025)
Halal products encompass not only food but also modest apparel, cosmetics, medicines, logistics, media, and other sectors that serve the global Muslim population. At the core of these sectors is the notion of halal integrity, which embodies Islamic ethical consumption by ensuring that products are religiously permissible and maintain transparency, hygiene, and fairness throughout the production chain. This study examines young customers, acknowledging them as a dynamic demographic whose understanding and decisions profoundly influence the future of the halal sector. The research aims to achieve three specific objectives: first, to identify the principal factors affecting young people's awareness of risks associated with halal products; second, to integrate qualitative and quantitative data into a cohesive halal risk register; and third, to create a risk management matrix that systematically classifies, assesses, and mitigates risks to halal integrity. The results indicate that halal-certified products, typically priced higher than non-certified options, exhibit greater susceptibility to risks, with an exposure rating of 0.76. This increased risk is associated not just with fraud and mislabeling but also with deficiencies in consumer awareness and supply chain oversight, which can erode confidence in halal certification. The study emphasizes the necessity of merging ethical considerations with risk management to preserve halal integrity, so ensuring customer confidence, protecting industry reputation, and responding to the increasing demand for halal products in both Muslim-majority and non-Muslim countries. The study emphasizes the value of raising young consumers' awareness of halal products and highlights the risks associated with their choice of halal goods.